Somalia : Second and Final Review Under the Staff-Monitored Program and Request for a New Staff-Monitored Program-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Somalia's Second and Final Review Under the Staff-Monitored Program (SMP) and Request for a new SMP. Program implementation through end-December 2016 and end-March 2017 was broadly satisfactory. In view of this performance and the remedial measures by the authorities to address shortcomings in performance under the first SMP, the IMF management agreed to the completion of the second and final review of the program. Risks to the program and the outlook are high, including the fragile security situation, weak institutional capacity, and major refugee and humanitarian crises. However, the authorities' continued commitment to the program and sustained and coordinated international support should help mitigate these risks.